SOSIALISASI KEMANDIRIAN PADA ANAK TERLANTAR (Studi Kasus Panti Asuhan Bayi dan Balita Fajar Harapan Kota Pekanbaru) - Jamilah, Milatul; ", Yoserizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research is done at the Fajar Harapan of Baby and Toddler Orphanage in Pekanbaru City. The purpose of this research is to find out and analyze about the meaning of independence and pattern of socialization has applied by caregivers to socialize the independence behavior of abandoned children. The focus of this research is a meaning of independence, the ways and patterns of socialization has applied by caregivers to socialize the independence behavior of abandoned children. This research uses a qualitative approach with descriptive analysis. The selection of informants in this study is done with a purposive sampling technique that is taking data from informants based on certain criteria. The informants of research are amounted to 5 people with the criteria of caregivers with long sizes of work and staying in the Fajar Harapan Orphanage. Data collection of techniques are used in this study was in-depth interviews, observation of participant, and documentation. The result of research was the independence is an attitude or ability shows that a child is able to do something to fulfill their own needs on the basis of self-ability. The process of socialization independence in abandoned children starts from a 2-year-old child by means of teaching, inducement, habits, using a model or example and reward. The socialization patterns has applied by caregivers is differently which is based on character, education and age including; the first informant and the second informant applies a pattern of democratic and authoritarian socialization, the third informant and the fourth informant applies a pattern of democratic socialization, and the fifth informant uses a pattern of democratic and permissive socialization. A form of self-reliance behavior in foster abandoned children have begun to take responsibility for the commandment a babysitter give them, a children are beginning to be able to make their own decisions, a children are sensitive to the environment and care for others, and abandoned children are able to engage in activities without help others.Keywords: Socialization, Independence, Abandoned Children